Arterial hypertension and thyroid function compensation: pharmacotherapy aspects - G. B. Selivanova (Кардиоваскулярная терапия и профилактика)
Based on literature data on arterial hypertension (AH) therapy in hypothyrosis patients, a need for investigating this issue considering pathogenesis of hypothyrosis-specific hemodynamic changes, is emphasized. The author presents original data on differential AH treatment, including АСГ inhibitor perindopril, in hypothyrosis patients. In this clinical group, perindopril as monotherapy or as a part of combined antihypertensive treatment, was effective in 83,3% of the patients. Therefore, perindopril could be used for pathogenetic AH therapy in hypothyrosis.